Problematika Pengaturan Persekusi Dalam Penerapan Hukum Pidana Di Indonesia - Rani Oslina Nainggolan; Erdianto Effendi; Davit Rahmadan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
Persecution is arbitrary hunting of a person or a number of people who are hurt, distressed orcrushed based on ethnicity, religion, race and political views. The establishment of criminal law is expectedto be able to overcome legal problems that occur in society. The existence of criminal sanctions is expectedto provide a deterrent effect to the perpetrators of criminal acts. There is no regulation in Indonesiancriminal law regarding acts of persecution, so that sanctions given to perpetrators have not been able to runoptimally and have not provided a deterrent effect. So that the laws that have been aspired have not yet beenrealized.The purpose of this essay is: First, to find out the problem of persecution arrangements in theapplication of criminal law in Indonesia. Second, to find out the ideal idea of legal regulation of persecutionin Indonesia. This type of research is normative legal research, in this case the author chooses research onthe principles of law, namely the principle of legality. The theoretical foundation used is the theory ofjustice, the theory of legal renewal, and the concept of crime.From the results of the problem research there are two main things that can be concluded. First, theproblem of the regulation of persecution in the application of criminal law in Indonesia is that there is noclear regulation by the Criminal Code or other laws and regulations concerning criminal acts ofpersecution. This is certainly not in line with the principles that apply in the Criminal Code, namely theprinciple of legality .Secondly, the ideal idea of legal regulation of persecution is that the perpetrators canbe held accountable for crimes and can be subject to criminal sanctions. Persecution which is a humanrights violation based on racial religion and political views. So it is necessary to have a legal policy thatregulates the act of persecution in a law.Based on this matter, Indonesia should make further rules regarding the criminal acts of persecutionin the form of laws and regulations such as laws on persecution and weighting penalties by givingappropriate sanctions to these crimes.Keywords: Crime, Persecution, Sanctions.